2018
DOI: 10.2174/1567201815666180226115503
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Influences of Carboxymethyl-β-Cyclodextrin on DNA Formulations Characteristics and Gene Transfection Efficiency

Abstract: pDNA/CM-β-CD complex has not only shown to be able to transfect COS 7 and SHSY5Y cell lines, but it gives a higher transfection efficiency than that produced by the TransIT-LT1 commercial transfection reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…DNA condensation is a prerequisite for successful gene delivery. Carboxymethyl-β-cyclodextrin has shown to be effective in gene delivery and our previous study 14 demonstrated that carboxymethyl-β-cyclodextrin has the ability to condense DNA at a molar ratio of 1:3 with 22% encapsulation efficiency. To investigate this further carboxymethyl-β-cyclodextrin (CD) was incorporated with cationic lipid (DOTAP), netural lipid (DOPE) and cholesterol to form liposomes to study the effect on gene cationic liposomes transfection and to evaluate the degree of gene encapsulation efficiency.…”
Section: Resultsmentioning
confidence: 91%
“…DNA condensation is a prerequisite for successful gene delivery. Carboxymethyl-β-cyclodextrin has shown to be effective in gene delivery and our previous study 14 demonstrated that carboxymethyl-β-cyclodextrin has the ability to condense DNA at a molar ratio of 1:3 with 22% encapsulation efficiency. To investigate this further carboxymethyl-β-cyclodextrin (CD) was incorporated with cationic lipid (DOTAP), netural lipid (DOPE) and cholesterol to form liposomes to study the effect on gene cationic liposomes transfection and to evaluate the degree of gene encapsulation efficiency.…”
Section: Resultsmentioning
confidence: 91%
“…] is a common redox indicator that is frequently used for the characterization of the DNA sensor assembling [25,33,34]. Moreover, it is a part of redox pair applied in the faradaic EIS technique for assessment of the conditions of electron exchange on the modified electrodes including electrochemical biosensors.…”
Section: Ferricyanide Ionmentioning
confidence: 99%
“…Thus, complexation of daunorubicin with β-cyclodextrin accelerated the intercalation of DNA [24]. Formulations with DNA and carboxymethyl-β-cyclodextrin showed high stability, indicating high incorporation of DNA within the macrocycle [25]. Pillar [5]arene derivatives were tested in DNA compactization [26] and assembling of nanocontainers in gene therapy [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, systems have been successfully engineered which allow for DNA condensation within the CD pocket [109]. Gene delivery can be achieved through the usage of carboxymethyl-β-cyclodextrin, a simple modification which is commercially available [110]. Some groups have had success delivering DNAzymes, which form 1:1 polyplexes with CD and can target and suppress genes of interest [107,111].…”
Section: Pure CD Vectorsmentioning
confidence: 99%